Beneficial Effect of the New Leptodophora sp. Strain on Development of Blueberry Microclones in the Process of Their Adaptation - Yulia S. Topilina; Evgeniya A. Luk‘yanova; Lubov B. Glukhova; Margarita N. Shurupova; Anna L. Gerasimchuk; Yulia A. Frank; Dmitry V. Antsiferov (Microorganisms, 2023)
The paper searches for new solutions for the development of highbush blueberry orchards (Vaccinium corymbosum L. (1753)) in Western Siberia. All species of the genus Vaccinium display special symbiotic mycorrhizal associations with root systems—ericoid mycorrhiza, which essentially enhances the formation of adventitious and lateral roots. For the first time, we obtained pure cultures of micromycetes associated with the roots of wild species of the family Ericaceae in the Tomsk region, Russia. With regard to the data of molecular genetic analysis of the ITS region sequence, we selected the BR2-1 isolate based on its morphophysiological traits, which was assigned to the genus Leptodophora. Representatives of this genus typically enter into symbiotic relationships with heathers to form ericoid mycorrhizae. We studied the effect of strain BR2-1 on the development of microclones of the highbush blueberry var. Nord blue during their in vitro adaptation and showed its beneficial effect on growth and shoot formation in young plants. Experiments performed using submerged and solid-state methods showed that the most optimal method for commercial production of BR2-1 is cultivation on grain sterilized by boiling, followed by spore washing.